Evaluation of morphological, agronomic, quality, and nutrient characteristics of sheep fescue (Festuca ovina L.) populations in semi-arid environments - Ünal, Sabahaddin; Efe, Berna; Mutlu, Ziya; Yeler, Erdal Eren; Mintaş, Hacer (Genetic resources and crop evolution, 2025)
The rangelands in semi-arid regions have deteriorated quickly because of mismanagement such as early, over, and late grazing. Sustainable improvement measures should be implemented on rangelands that have poor quality and low quantity. This study aims to enhance new cultivars with plant species of sheep fescue from the grass family that are delicious and long-lasting, as well as high-quality. To our knowledge, this is the first study in Anatolian semi-arid conditions, with the most genotypes (61 populations), the broadest range of subject areas (agro-morphological and quality traits), and the most investigated traits (14 in total). Agro-morphological and quality traits were identified in this nursery plots. For morphological traits, G-641 had the highest plant height (39.74 cm), and node number (3.0), among the examined genotypes. The highest fresh forage yield (285 g plant −1 ) the most important trait, was obtained from the G-625 population among all genotypes in two-year results. As considered quality traits, the G-632 population had the highest protein ratio with 21.06%, and at the same time, it possessed the lowest acid detergent fiber and neutral detergent fiber. In nutrient elements, the G-632, G-598, G-647, and G-596 had the highest calcium, phosphorous, potassium, and magnesium contents, respectively, and thus outperformed the control cultivars in these traits. At the beginning of the breeding program, it is necessary to select materials with characteristics such as plant height, internode distance, and the number of nodes closely related to high fresh grass yield for success and effectiveness.